49.2k views
4 votes
Use substitution to solve each system of equations -3x-y=7 x+2y=6​

User Elim
by
5.4k points

1 Answer

6 votes

Answer:

X = -4

Y = 5

Explanation:

There are two equations:

-3x-y=7 ........... (i)

x+2y=6 ........... (ii)

From equation (ii), we get

x = 6 - 2y ......... (iii)

By substituting the value of "x" in equation (i), we can get,

-3*(6 - 2y) - y = 7

or, -18 + 6y - y = 7

or, 5y = 7 + 18

or, 5y = 25

or, y = 25/5

y = 5

Putting the value of "y" in equation (iii),

x = 6 - 2*5

or, x = 6 - 10

x = -4

Therefore, the answer is x = -4, and y = 5

User Tom Bush
by
5.1k points